Managing Education and Training Payments (Recurring and Capital Costs) - Lyadi, Muslim; Andriani, Tuti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The quality of education is directly related to the excellence of education in an educational unit. In achieving excellence in good schools, it is necessary to pay attention to the quality of teachers, the quality of students, school norms and discipline, as well as education and training facilities and financing. The use of the terms education and training in an institution or organization is usually combined into training. The unit that handles employee training is usually called Pusdiklat (education and training center). Education and training can be seen as a form of investment. Therefore, every organization or agency that wants to develop, training for its employees must receive great attention. This study focuses on examining whether there is an influence of education and training financing management on the quality of an educational institution. The purpose of this writing is to describe and analyze the influence of education and training financing management on the quality of educational institutions. Education and training financing management plays an important role in determining the success of education and training programs. Sufficient and well-managed funding ensures that the training program can run in accordance with the stated objectives